Are we ready to implement a discard ban in the gulf of Cádiz? Stakeholders' perceptions. (June 2020) - Gamaza, MariAngeles; Torres, Maria Angeles; Acosta, Juan Jose; Erzini, Karim; Sobrino, Ignacio
Abstract: The European Union Regulation No 1380/2013 revising the Common Fisheries Policy (CFP) aims at addressing the by-catch and discarding problem in commercial fisheries by implementing the "Landing Obligation" of the regulated species by 2019. At present, the gulf of Cádiz (GoC) landing ports are not ready to comply with this regulation; a number of key issues identified need addressing. Within this framework, the present study focuses on the challenges of finding relevant and efficient management solutions, considering opinions from all relevant stakeholders involved in the trawl fishery. The approach taken in this study involves participatory meetings, questionnaire surveys and interviews with stakeholders, including fishers, local fishery managers, government administrators, national inspectors, non-governmental organizations (NGOs) and scientists. Furthermore, we visited the main fish auctions in the GoC and talked personally to animal sub-products companies regarding their interest in new opportunities based on resources discarded by the trawl fishery. To achieve the goal of improving the management of this specific fishery and to bring it in line with the requirements of the CFP, we conclude that an effective participation of the fishing industry at all stages is of vital importance. Indeed, we advocate that fisheries research efforts should be directed towards management strategies proposed by all relevant actors within the fishery. Highlights: One regulation should not be imposed on all fisheries; each case should be independently addressed. Knowledge of all stakeholders' perceptions could contribute to a more effective management system. Discard reduction measures acceptability depends on accounting the fishing industry sustainability.